2020
DOI: 10.1111/jfpp.14840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1‐methylcyclopropene (1‐MCP) on ripening and volatile compounds of blueberry fruit

Abstract: Blueberry fruit (Vaccinium spp. Berkeley) are popular with people due to the functional components, but they are perishable. The objective of the study was to evaluate the effect of 1-methylcyclopropene (1-MCP) with and without ethylene on ripening and volatile compounds of blueberry fruit. Sensory quality, physicochemical indexes, functional component, antioxidant activity, and principal component analysis of volatile compounds of fruit were detected. The present results indicated that application of ethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Nevertheless, DI and BI of samples treated with ethylene prior to 1-MCP was still observably lower than that of control, especially in later stage of shelf life. Analogously, Serradilla et al (2019) reported that 1-MCP showed a positive impact on DI in early-season sweet cherries "Burlat" that was similar with our previous results on kiwifruits and blueberries (Xu et al, 2020). Furthermore, both Wu et al (2016) and Chen et al (2016) reported a decrease in BI of 1-MCP-treated pears in comparison with the untreated samples.…”
Section: Effect Of Different Treatments On DI and Bisupporting
confidence: 84%
See 1 more Smart Citation
“…Nevertheless, DI and BI of samples treated with ethylene prior to 1-MCP was still observably lower than that of control, especially in later stage of shelf life. Analogously, Serradilla et al (2019) reported that 1-MCP showed a positive impact on DI in early-season sweet cherries "Burlat" that was similar with our previous results on kiwifruits and blueberries (Xu et al, 2020). Furthermore, both Wu et al (2016) and Chen et al (2016) reported a decrease in BI of 1-MCP-treated pears in comparison with the untreated samples.…”
Section: Effect Of Different Treatments On DI and Bisupporting
confidence: 84%
“…Ethylene biosynthesis is regulated by the activity of ACS and ACO, as well as expression of ethylene biosynthesis genes (Liu et al, 2009). In recent years, 1-methylcyclopropene (1-MCP), as an inhibitor of ethylene action, has played a positive role in extending the shelf life of postharvest fruit (Liu et al, 2018;Saba & Watkins, 2020;Xu et al, 2020). For example, treatment with 1-MCP can prolong storage time and maintain commodity value of peach (Wang, Wei, Chen, et al, 2020;Wang, Wei, Chen, et al, 2020), kiwifruit (Salazar et al, 2019), pear (Chen et al, 2016), jujube (Zhang et al, 2012), blueberry , durian (Thongkum et al, 2018), and apple (Zhou…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of ethylene in blueberry softening is still not clear as it has been confirmed by contrasting results of several studies (Table 1). Few articles (DeLong et al, 2003;Blaker and Olmstead 2014;Costa et al, 2014) do not show any significant effect of ethylene on fruit texture during ripening and storage, while others (Ortiz et al, 2018;Wang et al, 2020) ethylene (i.e., KmNO4 scrubber) and its perception (i.e., 1-MCP) resulted in textural improvements (Chiabrando and Giacalone, 2011;Ortiz et al, 2018;Wang et al, 2018a;Xue et al, 2020;Xu et al, 2020). In particular, 1-MCP treatment delayed the hemicelluloses solubilization in blueberry fruit (cv.…”
Section: Discussionmentioning
confidence: 99%
“…Similar inconsistencies regard the role of ethylene in regulating blueberry storability. Available results about increasing the fruit exposure to ethylene, for instance with ethephon or ethylene application (Poole et al, 1998;Costa et al, 2018;Wang et al, 2018b;Xu et al, 2020), or reducing the possible effect of ethylene applying ethylene scrubbers (Wang et al, 2018a;Álvarez-Hernández et al, 2019), 1-MCP (DeLong et al, 2003;Brackmann et al, 2010;MacLean et al, 2011;Blaker and Olmstead, 2014;Deng et al, 2014;Tao et al, 2017;Xu and Liu, 2017;Xu et al, 2020;Xue et al, 2020), or ozone (Song et al, 2003), indicated contrasting results and did not elucidate the role of ethylene on blueberry ripening.…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature and controlled ethylene concentration can delay the ripening of fruits and subsequently affect the aroma of horticultural crops. Compared with treatment at the beginning of picking, the application of the ethylene and 1-methylcyclopropene (1-MCP) not only preserved the freshness of stored blueberry fruits but also did not have a significant impact on aroma substances [ 71 ]. The degradation effect of ethylene was effectively neutralized by 1-MCP.…”
Section: Main Factors Affecting Fruit Aroma Synthesismentioning
confidence: 99%